Deterrence versus Reassurance: Implications of the Maritime Strategy for Norway. - Aabakken, Erling (1987)
The purpose of this analysis is to determine the impact on Norwegian security should NATO and the United States apply The Maritime Strategy to operational planning for the Norwegian Sea. The Maritime Strategy is a global strategy, which in competition for acceptance against the continental-coalition strategy, has to satisfy U.S. needs for counter the Soviet Union. Although much of the campaign for The Maritime Strategy has focused on the Norwegian Sea, the goal is global. The presence of NATO naval forces in the Norwegian Sea has been limited to the STANAVFORLANT and other allied forces during exercises. Recent exercises and force deployment demonstrate that NATO leaders have decided to increase allied presence in northern waters to counter Soviet Naval expansion. The 600-Ship U.S. Navy, beign built as the result of The Maritime Strategy campaign, gives NATO the possibility to increase NATO presence further and make such an aggressive strategy in this area more credible. Official Norwegian Security and Defense policy rests on the twin pillars of deterrence and reassurance, and if implemented, The Maritime Strategy has to fit into the constraints made up by these two pillars.